Message - Al-Shamahy, Prof. Dr. Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2020)
High-quality research is essential for our beloved UJPR to achieve its constitutional goal, that is, to help all peoples attain the highest possible standard of health. Research and evidence that research outcomes are critical components of improving health, our journal has always given high priority to research from developing countries. The primary importance of research for the journal has been determined to promote and conduct research in the field of health. The journal's strategy for research in health is based on the premise that health-promoting policies and practices around the world must be anchored in the best scientific knowledge. The mission of the strategy is that all partners must work together to harness science, technology and broader knowledge in order to produce research-based evidence and tools to improve global health. The journal's strategy is based on a number of key features: neutrality and independence; Global membership, unique and broad experience in public health and scientific research; Global normative role; adhere to evidence; the ability to invite scientists, researchers, scientific experts and other stakeholders to publish and benefit from the research published in the journal; The decision-making process should be guided by the principles of quality, impact and comprehensiveness of this research at the national, regional and global levels. Achieving such goals requires teamwork, and for this I appeal to all members of the journal to continuous sincere work and not leave the honorable brother, the journal editor in chief, to make the most of the effort to make the journal succeed and achieve its noble goals, as well as to deliver the journal to the prestigious position it deserves, as we all reach the delivery of the journal to Escopes in during the coming period - and I repeat here the title - a person is little by himself, much with his/her brothers/daughters.